STUDI LITERATUR: KOMPETENSI AUDITOR DAN KEAHLIAN SISTEM INFORMASI AUDITOR TERHADAP PEMBUKTIAN FRAUD - Masfa’ani, Rikhza; Ratnawati, Tri (Fakultas Ekonomi, 2024)
ABSTRACT The aim of this research is to clarify the impact of competence and independence on the quality of trial results through a literature review. This research population uses all research papers and studies related to the researcher's focus, namely competence and independence in the quality of research test results. The method used is a literature review using qualitative methods, carried out using digital skills from various sources. Several studies show that auditor competence has a significant positive influence on the quality of investigative audit results, and independence has a significant positive influence on the quality of investigative audit results. Several studies have found that there is no significant positive effect on independence. The impact on the quality of investigative audit results. Further research is needed to determine whether characteristics other than those described in this article can influence the quality of survey audit results. Keywords : Auditor Competency, Auditor Independence, Quality of Audit Results, Audit Investigation